2011
DOI: 10.1016/j.yexcr.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB inhibition compromises cardiac fibroblast viability under hypoxia

Abstract: Cardiac fibroblasts are reported to be relatively resistant to stress stimuli compared to cardiac myocytes and fibroblasts of non-cardiac origin. However, the mechanisms that facilitate their survival under conditions of stress remain unclear. We explored the possibility that NF-κB protects cardiac fibroblasts from hypoxia-induced cell death. Further, we examined the expression of the anti- apoptotic cIAP-2 and Bcl-2 in hypoxic cardiac fibroblasts, and their possible regulation by NF-κB. Phase contrast microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Earlier studies have stated that the role of the activation of NF-kB which is connected with the phosphorylation of IkBa and transport of p65 from the nucleus. 26,27 In the present study, it was found that linalool was able to inhibit the phosphorylation of IkB-a together with reduction of NF-kB in myocardial tissues. Thus, it has been suggested that the protective effects of linalool could be attributed to the attenuation effect which might be because of the signals of the inammation via inhibition of the NF-kB activation.…”
Section: Discussionsupporting
confidence: 51%
“…Earlier studies have stated that the role of the activation of NF-kB which is connected with the phosphorylation of IkBa and transport of p65 from the nucleus. 26,27 In the present study, it was found that linalool was able to inhibit the phosphorylation of IkB-a together with reduction of NF-kB in myocardial tissues. Thus, it has been suggested that the protective effects of linalool could be attributed to the attenuation effect which might be because of the signals of the inammation via inhibition of the NF-kB activation.…”
Section: Discussionsupporting
confidence: 51%
“…IAPs directly block the cleavage (and activation) of the caspases, thus inhibiting apoptosis [59]. Notably, c-IAP2 is up-regulated in hypoxia in an NF-κB-dependent manner [60].…”
Section: Hif and Apoptosismentioning
confidence: 99%
“…Using our model system we demonstrated that hypoxic pretreatment promoted the survival of CMs but not cardiac fibroblasts following H/R injury (Figures ). Cardiac fibroblasts are less sensitive to stress than CMs and are relatively resistant to pro‐apoptotic stimuli, including hypoxia, as seen here in the >2‐fold decrease in CM viability relative to the fibroblasts upon H/R injury. It is possible therefore that we did not observe an effect from hypoxic pretreatment on fibroblast viability because the hypoxic condition during the pretreatment period was of insufficient duration or severity to induce the initiation of prosurvival mechanisms in this cell type.…”
Section: Discussionmentioning
confidence: 73%